Insights from quantum chemical calculations into inner and outer-sphere complexation of plutonium(iv) by monoamide and carbamide extractants. Issue 3 (13th January 2021) - Failali, Abdelmounaim; Acher, Eléonor; Vallet, Valérie; Réal, Florent; Guillaumont, Dominique
Abstract : The strong influence of the structure of amide derivatives on plutonium extraction properties is rationalized from DFT calculations. Abstract : The strong influence of the structure of amide derivatives on their extraction properties has been demonstrated in several studies in the literature. To investigate and rationalize the influence of the nature and length of the monoamide alkyl chains on Pu(iv ) extraction/complexation, a theoretical study was performed using the Density Functional Theory (DFT) method in the scalar relativistic framework. For that, the geometries for the inner/outer-sphere complexes and interaction energies of [Pu(NO3 )4 ] and [Pu(NO3 )6 ] 2− with different ligands have been calculated. For both inner and outer-sphere complexes, it is found that the introduction of a bulky alkyl group on the carbonyl side strongly diminishes the complexation energy. This is fully consistent with monamide extraction properties. The influence of the bulkiness of the alkyl group is as or even more important for outer than for inner-sphere interactions. This result was unexpected when considering that there are less flexibility and stronger steric constraints in the inner sphere compared to the outer one. However, this can be attributed to specific electrostatic interactions between the two outer-sphere amide ligands and two nitrate ions of [Pu(NO3 )6 ] 2− . By increasing the polarity of the solution, such interactions diminish and the outer-sphere ligands move away from [Pu(NO3 )6 ] 2− . Consequently, the solvent effects were found to be very significant for outer-sphere complexation while rather small for inner-sphere complexation. This gives the key possibility to tune the substituent effect by changing the polarity of the solution. As for carbamide ligands, it was found that the weak interactions (dispersion) have remarkable effects on both inner and outer-sphere complexations.